JQuery mobile develop and design - Hadlock, Kris (Peachpit Press, 2012)
"Covering the latest version of the jQuery Mobile Framework, "jQuery Mobile: Develop and Design" teaches readers step-by-step how to get started, how to write code, and ultimately how to create mobile websites using the jQuery Mobile framework. The book is hands-on, with code examples (with corresponding on-line demos) and activities throughout."--WorldCat.